MARKETING STRATEGY IN INCREASING SALES TURNOVER IN THE EASTERN INDONESIA KIOSK BUSINESS (KTI) MAKASSAR CITY - Agus Syam; Muh. Nasrun Minallah; Asmayanti Asmayanti; Sudarmi Sudarmi (International Journal Labs, 2024)
Eastern Indonesia Kiosk (KTI) is one of the special store businesses that offers a variety of chicken products, such as slaughtered chicken, eggs, nuggets, and other needs related to processing chicken into delicious dishes.as the object of this study. The purpose of this study is to determine and analyze the marketing mix strategy in increasing sales turnover at the Eastern Indonesia Kiosk (KTI) Makassar City. The research method used is a qualitative descriptive method using SWOT analysis methods and data collection techniques through in-depth interviews, observations, and documentation related to marketing mix strategies which include products, prices, promotions and places and places by researchers in identifying strengths, weaknesses, opportunities and threats with the SWOT analysis method at the Eastern Indonesia Kiosk (KTI) Makassar City. Based on this study, the results of IFAS and EFAS showed strength with a score of 1.52 and weakness with a score of 0.75. While the EFAS results show opportunities with a score of 1.52 and threats with a score of 1.02. Based on the SWOT Analysis diagram, the East Indonesia Kiosk (KTI) Makassar City shows in diagram I by using the SO strategy, namely the company has opportunities and strengths so that it can take advantage of existing opportunities so that the strategy that can be applied is to support aggressive policy growth (growth oriented strategy) to increase sales turnover at the Eastern Indonesia Kiosk (KTI) Makassar City.